PkM di SMA Negeri 1 Pelangiran Kabupaten Indragiri Hilir: Permainan Tradisional untuk Mengurangi Kecanduan Game Online - Novri Gazali; Idawati Idawati; Romi Cendra; Raul Guswandi; Rapi Ardamis (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2022)
Contains the issue and focus of dedication, the purpose of dedication, dedication research methods / approaches / strategies, and the results of community service (250 words maximum). Problems with the use of online games have received a lot of attention at this time, especially in children and adolescents. The purpose of this Community Service activity is to implement traditional games in reducing online game addiction. This activity was carried out at SMA Negeri 1 Pelangiran, Indragiri Hilir Regency, Riau Province. The implementation of traditional game implementation activities in reducing online game addiction at SMA Negeri 1 Pelangiran was well followed by all students. Students are very enthusiastic in this activity, because apart from gaining knowledge about the dangers of online games, they can also compete in traditional games.